Lidar measurements during Aerosols99 - Voss, Kenneth J.; Welton, Ellsworth; Quinn, Patricia K.; Johnson, James; Thompson, Anne M.; Gordon, Howard R. (AGU, 2001)
The Aerosols99 cruise (January 14 to February 8, 1999) went between Norfolk, Virginia, and Cape Town, South Africa. A Micropulse lidar system was used almost continually during this cruise to profile the aerosol vertical structure. Inversions of this data illustrated a varying vertical structure depending on the dominant air mass. In clean maritime aerosols in the Northern and Southern Hemispheres the aerosols were capped at 1 km. When a dust event from Africa was encountered, the aerosol extinction increased its maximum height to above 2 km. During a period in which the air mass was dominated by biomass burning from southern Africa, the aerosol layer extended to 4 km. Comparisons of the aerosol optical depth (AOD) derived from lidar inversion and surface Sun photometers showed an agreement within ±0.05 RMS. Similar comparisons between the extinction measured with a nephelometer and particle soot absorption photometer (at 19 m altitude) and the lowest lidar measurement (75 m) showed good agreement (±0.014 km⁻¹). The lidar underestimated surface extinction during periods when an elevated aerosol layer (total AOD > 0.10) was present over a relatively clean (aerosol extinction < 0.05 km⁻¹) surface layer, but otherwise gave accurate results.